Kualitas Organoleptik Es Krim Santan - Lydia Fanny; Magdalena Magdalena; Thresia Dewi Kartini (Jurnal Kesehatan Manarang, 2021)
The results of Riskesdas 2018 show that the prevalence of malnourished under-five children in South Sulawesi is still high compared to the national figures and WHO targets. Makassar City has a higher number of children under five suffering from malnutrition than other cities/districts, namely 22.1% underweight, 25.2% stunting, and 9.4% wasting. Ice cream has a high nutritional value depending on the quality of the raw materials, so the raw materials used need to be known for certain. Coconut milk as a raw material for coconut milk ice cream has a high-fat content, the fat content makes the ice cream soft and of good quality. This study aims to determine the organoleptic quality of coconut milk ice cream. This type of experimental research is a completely randomized design (CRD), namely, there are 3 treatments of coconut milk with the addition of red bean and papaya pulp, namely F1=10g:50g, F2=20g:100g, and F3=30g:150g, each repetition 2 times, with F0 coconut milk without the addition of red bean pulp and papaya. Organoleptic quality was obtained from the organoleptic test of coconut milk ice cream to 40 untrained panelists at the Department of Nutrition of the Health Polytechnic of the Ministry of Health Makassar and of the Health Polytechnic of the Ministry of Health Banjarmasin. The results showed that the organoleptic quality in terms of color with p=0.001 and texture p=0.025 meant that there was an effect of adding red bean pulp and papaya. Meanwhile, from the aspect of aroma with p = 0.545 and taste p = 0.448, it shows that there is no effect of adding red bean porridge and papaya to coconut milk ice cream. The most acceptable coconut milk ice cream based on organoleptic quality was F1 (10g:50g) with a total score of 157.